2023
DOI: 10.1108/jpif-11-2022-0083
|View full text |Cite
|
Sign up to set email alerts
|

UK commercial real estate valuation practice: does it now build in sustainability considerations?

Abstract: PurposeThis paper investigates the extent to which commercial property valuers in the UK refer to Royal Institution of Chartered Surveyors (RICS) professional standards and guidance on the inclusion of sustainability in valuation reports. Data collection, analysis and reporting related to sustainability attributes is examined, as well as the perceived importance of these attributes to clients and any value impacts that are associated with them.Design/methodology/approachAn online survey of UK commercial proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Chmielewska et al [148] analyzed the investment transactions of residential real estate in five cities in Poland pre-and mid-pandemic and revealed a new preference among investors, which is to purchase properties located away from city centers and possibly anchor developments with the desire for larger space and better views. A study by Hossain et al [149] found that in some property valuers in the United Kingdom, sustainability in commercial real estate is more important for unit owners or occupants than for investors-this could not be said, however, of the entire population of property valuers in the United Kingdom. Contrary to these studies, post-pandemic investors in the Philippines significantly consider traditional notions in their property valuation (β = 0.691; p < 0.001) for their intention to invest in real estate.…”
Section: Discussionmentioning
confidence: 99%
“…Chmielewska et al [148] analyzed the investment transactions of residential real estate in five cities in Poland pre-and mid-pandemic and revealed a new preference among investors, which is to purchase properties located away from city centers and possibly anchor developments with the desire for larger space and better views. A study by Hossain et al [149] found that in some property valuers in the United Kingdom, sustainability in commercial real estate is more important for unit owners or occupants than for investors-this could not be said, however, of the entire population of property valuers in the United Kingdom. Contrary to these studies, post-pandemic investors in the Philippines significantly consider traditional notions in their property valuation (β = 0.691; p < 0.001) for their intention to invest in real estate.…”
Section: Discussionmentioning
confidence: 99%